Sobre o tipo penal de corrupção passiva na proteção de direitos fundamentais - Bertuol Junior, Altecir (2024)
This work was done to find out if, in view of the sanctioning provisions of the Law nº 8.429/92, the criminal type of passive corruption, from article 317 of the Penal Code, is necessary to the protection of fundamental rights in situations of requesting and receiving undue advantage by the agents of the State, in reason of the public function. To achieve the goal two different methodologies were applied: bibliographic search and documental research by collecting and examining judicial sentences. Therefore, sentences uttered by the Special Unit of Collective Actions from Cuiabá between October 25th 2021 and April 9th 2024 were collected. As a consequence of the inquiry, it was checked that, since they are all applied cumulatively, in the ideal field, the penalties of the Administrative Misconduct Law fulfill the criminal punishment purposes and offer appropriate protection to fundamental rights in view of the proportionality principle doble face, it was verified as well that in the concrete field the Sanctioning Administrative Law route safeguards those rights in an unsatisfying way, so that the penal type of passive corruption shows itself necessary to secure the human rights hit by the requesting and receiving undeserved benefit due to public service behaviors.